Portal de compras on-line para solnegsa - Toainga, L. (2010)
The modern life is strong, the utilization of the time is a challenge and a need that it must be covered for the different companies that offer services, especially those that are of massive concurrence. One of the places that sues for considerable time they are the supermarkets, specially to the moment to realize the payments in the cashier. The website that is hability electronic commerce are the best alternative to the purchases of supermarket worldwide. This document has as aim implement a website of electronic commerce for Solnegsa, a company that nowadays have a departmental shop and decides to implement website to offer major comfort to its customers on having realized his purchases comfortably from his home, avoiding the long tails of wait in cashier and the annoying move from his purchases to the home, avoiding also the use of ready money and offering the facility to the client of choosing the date and hour of the delivery. One presents the situational, technological and financial analysis of the Project where it is considered to be the development, implementation, advertising, benefits and economic proposal.